2018
DOI: 10.15405/epsbs.2018.07.75
|View full text |Cite
|
Sign up to set email alerts
|

Development Of Mind And Behavioural Control In Preschoolers With Different Mental Age

Abstract: The article considers the mutual relations of theory of mind (ToM), behavioural control and verbal mental age. It describes the development of ToM and behavioural control in preschool children.Behavioural control is assessed by the Day-Night task, the Test of Child Anxiety by Tamml, Dorky and Aman and a series of neuropsychological tasks. ToM is assessed by the following tasks: visual perspective understanding tasks, the task for the understanding of desires, the task for the understanding of "seeing leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The small size of our sample can limit our conclusions. However, in our previous study (Vilenskaya & Lebedeva, 2014) we found links between behavioral control and ToM in preschoolers in a sample of similar size. It is possible that in school age children the links between behavioral control and ToM are weaker and a small sample size is not enough for revealing these links.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The small size of our sample can limit our conclusions. However, in our previous study (Vilenskaya & Lebedeva, 2014) we found links between behavioral control and ToM in preschoolers in a sample of similar size. It is possible that in school age children the links between behavioral control and ToM are weaker and a small sample size is not enough for revealing these links.…”
Section: Discussionmentioning
confidence: 51%
“…An alternative explanation is that the differentiation of behavioral control and ToM functions takes place at primary school age. If in early childhood these two functions determined each other (as shown by our data from 3 to 5-year-old children in Vilenskaya & Lebedeva, 2014), then along with growing up these abilities become independent from each other, and their dynamics of development also differ. In general, ToM forms up to the age of 6 -7 years ; our data support this point of view), when self-regulation (behavioral control) continues to develop intensively .…”
Section: Discussionmentioning
confidence: 77%